2013
DOI: 10.1080/10796126.2013.764846
|View full text |Cite
|
Sign up to set email alerts
|

The parenting role of African-American fathers in the context of urban poverty

Abstract: This qualitative study examines low-income African American fathers’ perceptions of their parenting role and the strategies they employ to bring up children in poor urban neighborhoods. Focus groups and individual interviews were conducted with 36 fathers who had contact with their children at least twice a month. Men in the study expressed conventional views of their fathering roles as provider, nurturer, and teacher, but placed the most emphasis on “being there” for their children, as their financial circums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…For example, it has been suggested that cultures that emphasize autonomy and freedom promote values in individuals that are congruent with an internal locus of control orientation (Hamid 1994;McLaughlin and Saccuzzo 1997;Morris and Peng 1994). Minority groups in the US, in contrast, have been found in some studies to hold a more external locus of control, which is consistent with their collectivistic views (McCabe et al 2008;Norenzayan, and Lee 2010;Threlfall et al 2013). Extending this line of research to peer relationships, we found that culture influences the relationship between locus of control and peer relationships.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, it has been suggested that cultures that emphasize autonomy and freedom promote values in individuals that are congruent with an internal locus of control orientation (Hamid 1994;McLaughlin and Saccuzzo 1997;Morris and Peng 1994). Minority groups in the US, in contrast, have been found in some studies to hold a more external locus of control, which is consistent with their collectivistic views (McCabe et al 2008;Norenzayan, and Lee 2010;Threlfall et al 2013). Extending this line of research to peer relationships, we found that culture influences the relationship between locus of control and peer relationships.…”
Section: Discussionsupporting
confidence: 74%
“…An orientation towards external locus of control seems consistent with fatalistic beliefs that prevail in many Asian cultures (Norenzayan and Lee 2010;Yeh et al 2006) and in Mexican and other cultures with a strong Catholic tradition (McCabe et al 2008). In African-American cultures, having a more external locus of control orientation may be a way to deal with the disadvantages of poverty, unemployment, and racial discrimination (Threlfall et al 2013). In the domain of academic achievement, Asians and Asian Americans report greater internal control than Caucasian Americans regarding their academic performance.…”
Section: Introductionmentioning
confidence: 93%
“…Home environment has been recognized as having a lot of influence on academic performance. The family being the first and major agency of socialisation has a great influence and bearing on the development of the child (Threlfall, Seay and Kohl, 2013). Adeyemo (2006) as cited in Ganga and Chinyoka (2010) explained that the child's first place of contact with the world is the family.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Much research has shown the importance of strong family-school relations (Parveen, Noor-UL-Amin, and Nazir, (2013). Threlfall, Seay, and Kohl, (2013) ;Hafiz, Tehsin, Malik, Muhammad, and Muhammad, (2013) point out that parents have a fundamental responsibility to ensure that their children are at school and their school work is done. However, these authors note, many parents have never attended school and they cannot read, write or count properly.…”
Section: Parental Level Of Education/attitudes/ Support/ Resiliencementioning
confidence: 99%
“…More studies have qualitatively explored the experiences of African American males in their roles as fathers (Dallas & Chen, 1998;Hammond, Caldwell, Brooks, & Bell, 2011;Leavell et al, 2012;Marsiglio & Pleck, 2004;Moloney et al, 2009;Threlfall, Seay, & Kohl, 2013;White, 2006), but none were located that focused specifically on the process of "intergenerational change" among young dads whose own fathers were not in the home. By intergenerational change, I am referring to a deliberate shift in parenting practices from one generation to the next among fathers.…”
Section: Challenging the "Absentee Father" Paradigm And Intergeneratimentioning
confidence: 99%